PERSEPSI MAHASISWA TERHADAP PERILAKU SEKSUAL PADA MAHASISWA KOS DI LINGKUNGAN UNIVERSITAS RIAU KELURAHAN SIMPANG BARU PANAM PEKANBARU - Anita, Sri Ayu; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Highlights the difficulty in this research is ( 1 ) how perception students against sexual behavior the students in the neighborhood of university of staying in Riau corner new urban village Panam Pekanbaru ? ( 2 ) the factors that influence sexual behavior in the neighborhood of Riau university student dormitory new urban village, Pekanbaru Panam this? The purpose of this research is to find how perception student against student sexual behavior university dorm in the neighborhood of Riau corner new urban village Panam Pekanbaru and know the factors that affect sexual behavior in Riau university students who board in Pekanbaru corner panam new urban village . Respondents in the survey respondents was ten people consist of students, who was courting five men and one woman. Approach done on this research is a qualitative descriptive. The on the collection process uses in-depth interviews, observation and documentation.The results of research stated that ( 1 ) perception of staying in sexual behavior student against student board in corner new urban village Panam Pekanbaru can be measured based on ( a ) perception students who believe in regard to sexual behavior as courtship are low because the who believe can improve student learning achievements courtship on campus is only three people with perceived value 30 % ( b ) the perception that it is not good of having sexual behavior like going out relatively high because the lack of education that college students and six others with the religion of the 60 %. ( 2 ) of factors affect sexual behavior students board in a university campus lie in the Riau dominant: ( a ) the internal factor influences which are derived from within the individual influence happens to everyone , as a result give rise to desire syahwat in its interactions with the opposite sex so that elicit a feeling , and desire , of diverse sexual behavior as courtship . ( b ) external factors , who come from outside individual factors affecting sexual behavior of staying in Riau dominant university student in the neighborhood of derived from the influence of their peers , the gracied and supervision from the community , with the number of high as much as almost all the percentage of respondents said as many as 90 % influential , due to nearness emotional and ease information in access the internet and less control of the community leaders and mother of staying in.Keywords: Perception College Students, Sexual Behavior